HUBUNGAN KEPATUHAN ANTI RETROVIRAL THERAPY (ART) SATU BULAN TERAKHIR DENGAN KUALITAS HIDUP PASIEN HIV/AIDS DI RSUD DR. SOETOMO SURABAYA - Syahru Ramadhaan Unzila; Siti Rahayu Nadhiroh; Erwin Astha Triyono (Media Gizi Indonesia, 2016)
Anti Retroviral Therapy (ART) adherence infl uenced HIV/AIDS patient’s quality of life and otherwise quality of life influenced ART adherence positively, where the better quality of life of People Living With HIV/AIDS (PLWHA), the more ability of patient to adhere on their ART regiment. The purpose of this study was to analyze association between ART adherence and outpatient HIV/AIDS patient’s quality of life in four domains at RSUD Dr. Soetomo Surabaya. This study was an observational study with cross sectional design. Sample was 94 HIVAIDS patients’s outpatient and selected by using accidental sampling technique. The data was analyzed using Spearman correlation test. The result of study showed that most of HIVAIDS patients were 36–55 years old (53.2%), male (59.6%), normal nutritional status (42.6%), having high ART adherence in the last one month (79.8%), and having quality of life’s mean score in all domains ranged at 50–60 (30–40%). This study showed that there was an association between ART adherence in the last one month and quality of life in physical health (r =0.212, P = 0.040) and environment’s domain (r = 0.258, P = 0.012). It is suggested a comprehensive AIDS care program primarily with considering physical health and environment factors that could increase HIV/AIDS patient’s quality of life. It is suggested a longitudinal study with greater numbers of respondent and combine the use of measurement instrument to understand factors related to ARTadherence and quality of life.Keywords: sex, ART adherence, quality of life, nutritional status, age